If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13(x-8)=5x-33
We move all terms to the left:
13(x-8)-(5x-33)=0
We multiply parentheses
13x-(5x-33)-104=0
We get rid of parentheses
13x-5x+33-104=0
We add all the numbers together, and all the variables
8x-71=0
We move all terms containing x to the left, all other terms to the right
8x=71
x=71/8
x=8+7/8
| x*10x=8*16 | | 3(a+2)+2(2+3a=) | | 3x+7=4(x+1 | | 10x*x=8*16 | | 3x+31=6x+7 | | 57=2(1+5n)-5(1+6n) | | 3x2-5x-7=0 | | 2a+24+24=a+20 | | x16=5040 | | 10x(x)=8*16 | | y/18=6 | | 7(k-3=3k-5 | | h+(8.5)=-0.6 | | 2(x−4)=0 | | X-0.07x=180,000 | | 3q+5+2q=65 | | 135=201-y | | 1/3(3x-6)=9 | | -9.4+y/5=3.1 | | 200=-u+53 | | 12π=13πa | | 2y=y+57 | | 2x=3x-33 | | 27=13r2 | | 68-x=176 | | -3(7x-2)=-22-6x | | -15x12=-57 | | 1.03x=1500 | | -8x+3(2x-4)=9x-1 | | 42=22-6x | | x+12*4=2x-90 | | 8n-(-2)÷7=6 |